2012
DOI: 10.1074/jbc.m112.391441
|View full text |Cite|
|
Sign up to set email alerts
|

Sumoylation Is Important for Stability, Subcellular Localization, and Transcriptional Activity of SALL4, an Essential Stem Cell Transcription Factor

Abstract: Background: SALL4 is a key stem cell transcription factor that transactivates OCT4. Results: SALL4B is modified by sumoylation. Conclusion: Sumoylation plays an important role in regulating SALL4B stability, subcellular localization, and transcriptional activities. Significance: Sumoylation functions a major post-translational mechanism for regulating stem cell transcription factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Expression of SALL4B mutants with deletions of 3 lysine-rich regions (fragments of 258-317, 127-156, or 578-601) did not cause an apparent change in its subcellular localization compared with the wild-type counterpart. Moreover, mutations (4R) of those lysine residues required for SUMO-modification 11 did not affect the subcellular localization either. However, when lysine 64 was mutated into arginine (K64R), HA signals were detected primarily in the cytosol (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Expression of SALL4B mutants with deletions of 3 lysine-rich regions (fragments of 258-317, 127-156, or 578-601) did not cause an apparent change in its subcellular localization compared with the wild-type counterpart. Moreover, mutations (4R) of those lysine residues required for SUMO-modification 11 did not affect the subcellular localization either. However, when lysine 64 was mutated into arginine (K64R), HA signals were detected primarily in the cytosol (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…10,11 SALL4A is spliced from all 4 exons and encodes a protein containing 8 C2H2 zinc-finger domains. However, SALL4B lacks a large portion of exon 2 and encodes a protein containing 6 C2H2 zinc finger domains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sumoylation plays a role in regulating the subcellular localization of target proteins [25][26][27][28][29] To determine whether sumoylation played a role in regulating subcellular localization of Mus81, HeLa cells were transfected with GFP-tagged WT Mus81 or its Mus81-5R for 48 h. Cells were then fixed and stained with antibody against GFP. Fluorescence microscopy showed that both GFP-Mus81 and GFP-Mus81-5R was primarily located to the nucleus, and when the expression level was high, GFP-Mus81 and GFP-Mus81-5R mutant were enriched in nucleoli during interphase (Fig 3S).…”
Section: Sumo-resistant Mutant Induces Misaligned Chromosomes In Mitomentioning
confidence: 99%